Influence of fuel distribution on co-combustion of sludge and coal in a 660 MW tangentially fired boiler. (5th June 2023) - Wei, Daining; An, Dong; Wang, Tao; Zhang, Huicong; Guo, Yonghong; Sun, Baomin
Graphical abstract: Highlights: Increasing sludge burners' height reduces the effect on temperature distribution. Sludge intensifies incomplete combustion in the main combustion region. Co-combustion with 20% sludge let the heat flux decrease by about 6%. Feeding sludge from the top burners has the least impact on co-combustion. Abstract: The distribution method of coal and sludge is an important factor affecting co-combustion, but few studies have been carried out in most papers. The influence of different fuel distribution methods for municipal sewage sludge and coal on co-combustion in a furnace was studied using numerical computational fluid dynamics simulations in this paper. In the considered cases, the burners that inject sludge were artificially altered, while the masses and contents of sludge and coal remained unchanged. The combustion temperature, combustion characteristics, and the heat of the boiler were analysed. The concentrations of CO, CO2, and volatile matter were used as characteristic parameters. The conclusion shows that the co-combustion temperature in the main combustion region inevitably decreases compared to coal mono-combustion regardless of the fuel distributions being used. When coal and sludge are premixed, the furnace temperature distribution is more uniform. However, premixing has a greater influence on the boiler heat flux. Feeding sludge into the furnace from the top layer of burners individually can effectively reduce the adverse impact of premixed combustion, and the total heat flux of the furnace is reduced by 4.8%, the heat flux decreased by about 6% for other distribution methods. Considering the broad prospects of sludge co-disposal in boilers, these findings provide guidance and suggestions for the co-combustion of sludge and coal, and they provide theoretical support for the efficient operation of boilers.